Fatigue, pain interference, and psychiatric morbidity in multiple sclerosis: The role of childhood stress - Polick, Carri S.; Ploutz-Snyder, Robert; Braley, Tiffany J.; Connell, Cathleen M.; Stoddard, Sarah A. (PLOS ONE, 2023)
Background Multiple sclerosis (MS) is a progressive, autoimmune disease of the central nervous system that affects nearly one million Americans. Despite the existence of immunomodulatory therapies to slow physical and cognitive disability progression, interventions to ameliorate common symptoms of MS, including fatigue and pain, remain limited. Poor understanding of risk factors for these symptoms may contribute to treatment challenges. In recent years, childhood stress has been investigated as a risk factor for chronic autoimmune conditions including MS; yet remarkably few studies have investigated the relationship between childhood stressors and chronic MS symptoms. Our aim was to examine clusters of stressors and three key features of MS: fatigue, pain interference, and psychiatric morbidity. Methods Cross-sectional data were collected from a sample of People with MS (PwMS) via a national web-based survey that assessed the presence and type of childhood stressors and MS clinical features. Hierarchical block regression was used to assess associations among emotional, physical, and environmental childhood stressors and three clinical features commonly experienced by PwMS. Results N = 719 adults with MS (aged 21–85) completed the survey. Childhood emotional and physical stressors were significantly associated with overall presence of fatigue (p = 0.02; p<0.03) and pain interference (p<0.001; p<0.001) in adulthood, as well as the magnitude of both outcomes. Environmental stressors (p<0.001), in addition to emotional (p<0.001) and physical (p<0.001) stressors were significantly associated with psychiatric morbidity in PwMS. Conclusion Childhood stress may predict fatigue, psychiatric morbidity, and pain in adults with MS. Further research is needed to show cause and effect; however, if an association exists, strategies to mitigate the impact of childhood stress could offer new pathways to reduce the severity of these symptoms. Broadly, this work adds to the body of evidence supporting upstream preventive measures to help address the stress on children and families.